Determinant factors of customers’ purchase intention on the usage of travel shopping application - Leonytha Meriana; Kurniawati Kurniawati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Nowadays, online reservations to fulfill traveling needs have been widely expanded. Existing travel applications have multiple offerings to maintain customers or grab potential buyers. Therefore, it is essential to identify determinant factors of customers’ purchase intention on online travel shopping application usage. This study applied the Technology Acceptance Model, Diffusion of Innovation Theory, and Theory of Planned Behavior as theoretical perspective guidance. There were 253 responses collected via an online survey. The data were analyzed using structural equation modeling (SEM). The result of this study showed that purchase intentions (PIN) were determined by communicability (CMB), attitude (ATD), and perceived behavioral control (PBC). Unlike PBC, which directly relates to PIN, brand awareness (BAW) did not contribute directly but was fully mediated by CMB. In addition to that, BAW did have a positive association with CMB. Meanwhile, ATD on the usage of travel apps was prevalently formed by perceived relative advantages (PRA) and perceived technological congruence (PTC). ATD also played a mediating role between PRA and PIN. However, it did not apply between PTC and PIN. These results may help the travel providers focus on strategies to generate the PIN.